Variable Stiffness Biological and Bio-Inspired Materials - Saavedra-Flores, E (2013)
This article reviews the main mechanisms of stiffness variation typically found in nature. The temporal changes in stiffness may be fully or partially reversible, or completely irreversible, and can be very slow or fast in time depending on the strategy adopted to alter the mechanical properties. It is also possible to observe changes in the stiffness in order to recover the original mechanical properties in damaged natural materials by means of self-healing mechanisms. In addition to stiffness variations in time, natural materials can also exhibit stiffness changes in space. These variations can be represented by alterations in the spatial distribution of the microscopic constituents across multiple hierarchical scales, from very small physical scales to large macroscopic dimensions. In order to optimise the strength and multifunctionality of these materials, spatial changes can also occur over larger areas at one single scale. In addition, several examples are provided to illustrate how natural materials have been exploited further in order to develop new bio-inspired materials. © 2012 The Author(s).